(3TQM GdEaUGM Yf dH GdahGFO hGdJdNjU hGdeUHGMs - (3GdnZpqRj GdYGeQj GdbQTj GdOeTbqj, CHh GdecGQe, fLe GdOjf, eMeO Hf eMeO Hf eMeO, (B1061 (3g`s ((3NVQ GHf GdTGQMs)
(3ChdgG (B:s
(3MeOG dQH Ndb GdEfSGf (B*** (3Ydeg HaVdg GdHjGf , SHMGfg ehdi HOjYG cQeg (B*** (3YeJ YWGjGg hLeJ fYegs
(3BNQgG (B:s
(3Ke UdGJg Ydi GdeNJGQ (B*** (3eMeO hBdg GdCWgGQ , hUMHg GdeMHjf hGdSdGe (B*** (3hfSCd Gddg dfG MSf GdNJGes
(3hgPg fSNI efbhdI ef fSNI GdeDdas
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 7 / 63s
(3eYLe GdeDdajf(B: 3 / 685s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3GdHdGZIs